Regulating Gut Microbiome: Therapeutic Strategy for Rheumatoid Arthritis During Pregnancy and Lactation - Yao Yao; Xiaoyu Cai; Weidong Fei; Fujia Ren; Fengmei Wang; Xiaofei Luan; Fengying Chen; Caihong Zheng (Frontiers in Pharmacology, 2020)
Rheumatoid arthritis (RA) is an autoimmune disease characterized by synovial inflammation and bone destruction. Microbial infection is considered to be the most important inducement of RA. The pregnancy planning of women in childbearing age is seriously affected by the disease activity of RA. Gut microbiome, related to immunity and inflammatory response of the host. At present, emerging evidence suggested there are significant differences in the diversity and abundance of gut microbiome during pregnancy and lactation, which may be associated with the fluctuation of RA disease activity. Based on these research foundations, we pioneer the idea of regulating gut microbiome for the treatment of RA during pregnancy and lactation. In this review, we mainly introduce the potential treatment strategies for controlling the disease activity of RA based on gut microbiome during pregnancy and lactation. Besides, we also briefly generalize the effects of conventional anti-rheumatic drugs on gut microbiome, the effects of metabolic changes during pregnancy on gut microbiome, alteration of gut microbiome during pregnancy and lactation, and the effects of anti-rheumatic drugs commonly used during pregnancy and lactation on gut microbiome. These will provide a clear knowledge framework for researchers in immune-related diseases during pregnancy. Regulating gut microbiome may be a potential and effective treatment to control the disease activity of RA during pregnancy and lactation.